Epidemiology of mortality related to Chagas' disease in Brazil, 1999-2007. - Francisco Rogerlândio Martins-Melo; Carlos Henrique Alencar; Alberto Novaes Ramos; Jorg Heukelbach (Public Library of Science (PLoS), 2012)
Background Chagas' disease is an important neglected public health problem in many Latin American countries, but population-based epidemiological data are scarce. Here we present a nationwide analysis on Chagas-associated mortality, and risk factors for death from this disease. Methodology/principal findings We analyzed all death certificates of individuals who died between 1999 and 2007 in Brazil, based on the nationwide Mortality Information System (a total of 243 data sets with about 9 million entries). Chagas' disease was mentioned in 53,930 (0.6%) of death certificates, with 44,537 (82.6%) as an underlying cause and 9,387 (17.4%) as an associated cause of death. Acute Chagas' disease was responsible for 2.8% of deaths. The mean standardized mortality rate was 3.36/100.000 inhabitants/year. Nationwide standardized mortality rates reduced gradually, from 3.78 (1999) to 2.78 (2007) deaths/year per 100,000 inhabitants (-26.4%). Standardized mortality rates were highest in the Central-West region, ranging from 15.23 in 1999 to 9.46 in 2007 (-37.9%), with a significant negative linear trend (p = 0.001; R(2) = 82%). Proportional mortality considering multiple causes of death was 0.60%. The Central-West showed highest proportional mortality among regions (2.17%), with a significant linear negative trend, from 2.28% to 1.90% (-19.5%; p = 0.001; R(2) = 84%). There was a significant increase in the Northeast of 38.5% (p = 0.006; R(2) = 82%). Bivariable analysis on risk factors for death from Chagas' disease showed highest relative risks (RR) in older age groups (RR: 10.03; 95% CI: 9.40-10.70; p<0.001) and those residing in the Central-West region (RR: 15.01; 95% CI: 3.90-16.22; p<0.001). In logistic regression analysis, age ≥30 years (adjusted OR: 10.81; 95% CI: 10.03-10.65; p<0.001) and residence in one of the three high risk states Minas Gerais, Goiás or the Federal District (adjusted OR: 5.12; 95% CI: 5.03-5.22, p<0.001) maintained important independent risk factors for death by Chagas' disease. Conclusions/significance This is the first nationwide population-based study on Chagas mortality in Brazil, considering multiple causes of death. Despite the decline of mortality associated with Chagas' disease in Brazil, the disease remains a serious public health problem with marked regional differences.